PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS V MELALUI MODELPEMBELAJARAN PROBLEM BASED LEARNING TEMA 8 DI SD 9 GONDOSARI - Cici’ Istahiyyatun Nisa'; Choirul Huda; Joko Susanto (Universitas Negeri Medan, 2021)
Abstract :Improving Learning Outcomes Through the Problem Based Learning Model for Class V Student Theme 8 at SD 9 Gondosari. The background of the research is that there are several fifth grade students of SD 9 Gondosari for the 2020/2021 academic year who are less active in learning, so that learning outcomes are below the KKM. The problem in this study is how to improve the learning outcomes of fifth grade students through the Problem based Learning model at SD 9 Gondosari, Kudus Regency in the 2020/2021 academic year. This study aims to describe the implementation of the